Comparison of nutritional quality and sensory acceptability of biscuits obtained from native, fermented, and malted pearl millet (Pennisetum glaucum) flour. (1st October 2017) - Adebiyi, Janet Adeyinka; Obadina, Adewale Olusegun; Adebo, Oluwafemi Ayodeji; Kayitesi, Eugenie
Highlights: Pearl millet flour was fermented and malted. Fermentation and malting of pearl millet increased the nutritive value of flour and biscuit. Malting and fermentation of pearl millet increased essential amino acids of flour and biscuit. Fermented and malted pearl millet are potential materials for gluten-free products. Abstract: The effects of fermentation and malting on the proximate composition, mineral content, amino acids and total phenolic content of pearl millet flour and biscuits were studied. Consumer tests of the biscuits samples were also done using two sets of panelists. The results showed that fermentation and malting improved the crude fiber, crude protein, carbohydrate and energy values of the pearl millet flour. For the biscuit samples, the fermented and malted biscuits had higher moisture, crude protein, crude fiber and energy value with lower fat and ash content as compared to the biscuits obtained from native flour. Fermentation and malting were further observed to increase majority of the essential and non-essential amino acids. Consumer tests among the different set of panelists showed differences in the loading patterns as observed through principal component analysis. In conclusion, this study shows that fermentation and malting improves nutritional, health composition of pearl millet flour as well as the sensorial acceptability of subsequent biscuits.